KAJIAN HADIS DI BANTEN: Studi Pada Pondok Pesantren Masa Reformasi Dekade Ke-2 - Endad Musaddad (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2016)
As a basis on which the dissemination of Islam in Indonesia has laid over 500 years, Pesantren (Islamic boarding educational institution) has thought various Islamic disciplines, including hadis (prophetic tradition). There has been abundance of hadis literatures to be thought in Pesantrens -to mention some of them- such as Bulûgh al-Marâm, Riyâḍ al-Ṣâliḥîn, al-Aẓkâr, Ṣaḥîḥ al-Bukhârî, Ṣaḥîḥ Muslim, etc. All of these books together with the learning activities have raised particular academic ambiences in Indonesia’s Muslim societies.Compared to another disciplines of Islamic studies, such as Islamic Jurisprudence, Qur’anic exegesis, and Arabic language, hadis studies in Pesantrens unfortunately can be deemed as in stagnancy, even in this time. The fact about the limited number of distinguish scholar on the discipline confirms this claim. This writing is aimed at portraying the map of learning development of hadis discipline in several Pesantrens in the province of Banten through hadisliteratures, as well as the methods of learning and factors that slow down the study of hadis.